1967
DOI: 10.1085/jgp.50.9.2177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of External Calcium Deprivation on Single Muscle Fibers

Abstract: Deprivation of external calcium causes sudden potentiation of the twitch response of single muscle fibers. The potentiation was 64 4-8 %. Potentiation is simultaneous with membrane depolarization occurring after Ca +÷ removal. This depolarization amounted to 9 4-2 my. Ca ++ removal also alters the action potential. 3 rain after calcium withdrawal, action potential amplitude fell by 36 4-3 my; maximum rates of rise and fall of the spike decreased by 55 4-5 and 63 4-5 % respectively. Changes in shape of the A. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 26 publications
(36 reference statements)
12
45
0
Order By: Relevance
“…On the other hand, the peak tension of the secondary component was rapidly inhibited by the Ca2+ reduction, in contrast to the potentiation of the peak tension of the initial component. The result that shows the initial component of the contractures being potentiated at the initial stage of the Ca2+ reduction is in agreement with that of CAPUTO and GIMENEZ (1967), who reported that twitch tension and K contracture tension were strongly enhanced within 2 min when single muscle Japanese Journal of Physiology fibers were exposed to low Ca2+ solutions. In addition, the result that shows the peak tension of the initial component being inhibited at 20 min after Ca2+ reduction is comparable with those of FRANK (1960) and KOSAKA et al (1977).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the peak tension of the secondary component was rapidly inhibited by the Ca2+ reduction, in contrast to the potentiation of the peak tension of the initial component. The result that shows the initial component of the contractures being potentiated at the initial stage of the Ca2+ reduction is in agreement with that of CAPUTO and GIMENEZ (1967), who reported that twitch tension and K contracture tension were strongly enhanced within 2 min when single muscle Japanese Journal of Physiology fibers were exposed to low Ca2+ solutions. In addition, the result that shows the peak tension of the initial component being inhibited at 20 min after Ca2+ reduction is comparable with those of FRANK (1960) and KOSAKA et al (1977).…”
Section: Resultssupporting
confidence: 91%
“…In addition, the result that shows the peak tension of the initial component being inhibited at 20 min after Ca2+ reduction is comparable with those of FRANK (1960) and KOSAKA et al (1977). CAPUTO and GIMENEZ (1967) noticed the potentiating effect as the short term effect of the Ca2+ reduction. With respect to this, the inhibitory effect of Ca2+ reduction previously reported by FRANK (1960) and by KOSAKA et al (1977) and the effect observed in the present paper may be regarded as the long term effect of Ca2+ reduction.…”
Section: Resultssupporting
confidence: 77%
“…These experiments were carried out following the procedure of Hodgkin & Horowicz (1960). prolonged contractile responses represent the time necessary for the activator concentration in the myoplasm to be reduced from a supramaximal to a maximal concentration. Suggestive but not conclusive evidence against the idea that the spontaneous relaxation of potassium contractures was due to exhaustion of a store of activator available for release was obtained by changing differently the time course 187 C. CAPUTO AND P. F. DE BOLANOS of these responses by several experimental procedures (Caputo & Gimenez, 1967;Caputo, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence for the role of ECCE in normal use-dependent physiology and pathophysiology of adult skeletal muscles may have been described in earlier studies but were underappreciated. For example, the rate of relaxation of contractures after prolonged applications of extracellular K ϩ was faster in the absence of extracellular Ca 2ϩ than in its presence (Caputo and Gimenez, 1967), whereas brief depolarization in Ca 2ϩ -free solutions was not different from the response in Ca 2ϩ -replete external medium (Caputo and Gimenez, 1967;Grabowski et al, 1972). More recently, age-related denervation of fast skeletal muscle was found in senescent mice, and muscle fibers isolated from them were found to show dependence on extracellular Ca 2ϩ to maintain tetanic force (Payne et al, 2007).…”
Section: Downloaded Frommentioning
confidence: 99%